ANALISA DAMPAK KEBERADAAN PABRIK GULA AREN MASARANG TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT KECAMATAN TOMOHON SELATAN - Einstein Zetly Z.S. Karundeng; Theodora Katiandagho; Esry O.H. Laoh (Universitas Sam Ratulangi, 2015)
SUMMARY Development of the industrial sector as part of the process of national development in improving economic growth has brought changes to the lives of South Tomohon sub district community. These changes include the impact of industrial development on the socio-economic and environment industry, which includes livelihood from agriculture into industry and comDAMPmerce, ompacts are opening wider employment opportunities both for local people and migrants. Village residents Pangolombian state and Village Tondangow before the Palm Sugar Factory Masarang generally have livelihood agriculture and fisheries sector. The emergence of palm sugar factory Masarang a powerful magnet, attracting labor in both the village and the District of South Tomohon, about cultivation Good palm plant palm so that productivity is increases Einstein Zetly Z. S. Karundeng, 2015. Analisa Dampak Keberadaan Pabrik Gula Aren Masarang Terhadap Kondisi Sosial Ekonomi Masyarakat Kecamatan Tomohon Selatan, (Dibawah Komisi Bimbingan : Theodora Katiandagho, sebagai Ketua dan Esry O.H. Laoh sebagai Anggota